THE IMPLEMENTATION OF THE PROBLEM-BASED LEARNING (PBL) MODEL TO IMPROVE THE ACTIVENESS AND LEARNING OUTCOMES OF GRADE XI STUDENTS AT MAS ATTAQWA PUSAT PUTRI BEKASI - Ilyasa, Zuhriyah; Aripin, Syamsul (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
This classroom action research aims to improve the activeness and learning outcomes of eleventh-grade students at MA Attaqwa Pusat Putri Bekasi in the subject of marriage (fikih) through the implementation of the Problem Based Learning (PBL) model. This research was motivated by the low enthusiasm and activeness of students in fikih learning, which impacted the low psychomotor and affective learning outcomes. The subjects of the research were 20 female students from class XI.2 MA Attaqwa Pusat Putri. The study was conducted in two cycles, with each cycle including planning, action implementation, observation, and reflection. Data was collected through student activeness observation sheets and learning outcome tests (pre-test and post-test). Data analysis utilized descriptive percentage techniques. The results showed an increase in student activeness across various aspects, such as listening activities (from 86% to 88%), oral activities (from 45% to 61%), and visual activities (from 35% to 78%). Furthermore, there was an increase in the average learning outcomes score from 88 in cycle I to 97 in cycle II, as well as an increase in the